Mo Farah : Twin Ambitions : My Autobiography - Farah, Mo (London Hodder & Stoughton, 2013)
This is the boy from Mogadishu, Somalia, who came to Britain at the age of 8, leaving behind his twin brother, with a few words of English and wanting to play for Arsenal. Fortunately his PE teacher spotted his turn of speed on the pitch and began to ease this human cheetah towards the racetrack. This is Mo Farah's autobiography.
Include Color Illustrations and Index.
Mo Farah : My Autobiography.
Keywords: Great Britain -- Farah, Mo, 1983- -- Somalia -- Long-distance runners -- Runners (Sports)